KONTRUKSI MAKNA PERKAWINAN SASUKU DI KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Rahmat Alpian. R; Noor Efni Salam (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Society Sub District of Kuantan Mudik sasuku prohibit marriage, because marriage is sasuku customs that should not be done by local people, but now has anyone done the sasuku marriage. The occurrence of marriage in the District of Kuantan Mudik sasuku raises a variety of meanings partner about why they do sasuku marriage. The purpose of this study was to determine the motive of the couple to marital sasuku, to know how to interpret marriage couples sasuku, to find a marriage partner communications experience sasuku in Sub District Kuantan Mudik District Kuantan Singingi Riau Province.This study uses qualitative research methods with the presentation of descriptive analysis. informants of this research is a marriage partner sasuku, traditional leaders, parents and those closest partner, chosen by purposive sampling. Data collection techniques used were observation, interviews, and documentation. technical validity of the data used in this study is an extension of participation and triangulation..The results obtained show that the motive for the couple to marital sasuku in Sub District Kuantan Mudik consists of motifs past the mutual love between both spouses, consent obtained from both parents, and promiscuity, while the motif future of the desire not excluded from tribes, accepted by society, and niniak mamak not hold a marriage certificate. Couple sasuku interpret marriage in the District of Kuantan Mudik as a wedding performed by couples of the same tribe, but legitimate customs violations by religion, customs penglanggaran who will be penalized, it is taboo to do. Sasuku marriage partner communications experience in the district of Kuantan Mudik consists of the positive experience they have never experienced and negative experiences that they often become the topic of conversation, in the event of their violation rate is often used as measures that are not exemplary